Systemic Treatments for Metastatic Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer: Old Certainties and New Frontiers - Alessandro Rizzo MD; Antonio Cusmai MD; Raffaella Massafra PhD; Samantha Bove PhD; Maria Colomba Comes PhD; Annarita Fanizzi PhD; Gennaro Gadaleta-Caldarola MD; Donato Oreste MD; Alfredo Zito MD; Francesco Giotta MD; Vito Lorusso MD; Gennaro Palmiotti MD (Cancer Control, 2022)
Epidermal growth factor receptor 2 (EGFR2, also known as HER2) overexpression and/or amplification confers a more aggressive clinical behavior but also represents a therapeutic opportunity for targeted therapies in breast cancer (BC). Over the last 2 decades, the prognosis of HER2-positive metastatic BC patients has improved due to the introduction of anti-HER2 agents including trastuzumab and novel, emerging drugs and combinations such as trastuzumab deruxtecan and tucatinib – trastuzumab - capecitabine. Herein, we provide a critical overview of current clinical recommendations and emerging treatment options for metastatic HER2-positive BC, especially focusing on recently presented and published clinical trials in this setting.